Myopic Progression of Children in RSUP Dr M Djamil During COVID-19 Pandemic - Devilen, Yuki San; Sayuti, Kemala; Desmawati, Desmawati (Jurnal Ilmu Kesehatan Indonesia, 2023)
Background: Myopia (nearsightedness) is an eye condition when a far object reflection is focused in front of the retina without accommodation, so far object cannot be seen clearly. The elongation of the eye's axial length primarily causes myopia. Lack of outdoor activities and excessive near work (screentime) during home confinement duringthe COVID-19 pandemic have increased the risk of myopia development, primarily in school children. Objective: This study aims to see children's myopic progression during the COVID-19 pandemic. Methods: This research was an observational analytic study by a retrospective cohort about children's myopic progression based on the difference between the spherical equivalent (SE) of 34 patients in RSUP Dr. M. Djamil from before (September 2019–February 2020) followed up to late (September 2021–February 2022) of COVID-19 pandemic from their medical records. Results: The results showed that myopic progression majorly occurredin children who were females (47.0%), had myopic parents (67.6%), ≥ 2 hours of outdoor activity (61.7%), > 5 hours of screentime (79.4%); with slow annualized myopic progression (61.7%). The median of SE from before and late the COVID-19 pandemic are -4.00 (-16.00 – -0.25) D and -4.62 (-17.00 – -0.25) D respectively; p<0.001. Conclusion: Children did have myopia worsening during the COVID-19 pandemic. Keywords: Myopia, Progression, COVID-19, Children, Spherical Equivalent